2012
DOI: 10.1080/02703149.2012.634714
|View full text |Cite
|
Sign up to set email alerts
|

Ni Pardo, Ni Prieto: The Influence of Parental Skin Color Messaging on Heterosexual Emerging Adult White-Hispanic Women's Dating Beliefs

Abstract: The influence of Hispanic parental processes on daughters' intimate relationships have been widely studied in the psychology literature. However, although skin color values have been found to directly inform dating preferences, research examining the influence of parental skin color beliefs is non-existent. Thirty-four emerging adult Hispanic women participated in this qualitative study which examined their beliefs about parental skin color beliefs on dating preference decision-making processes. The study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…One study of college students' intercultural dating behaviors and attitudes found that 90% of White men and 70% of Black men viewed Latinas as an attractive intercultural dating partner, whereas 60% of White men and 52% of Latino men viewed Black women as an attractive intercultural dating partner [31]. Much of this may be accounted for by the fact that many Latinas match the idealized popular image of American female beauty [26,31,32].…”
Section: Latino/a Students and Intercultural Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of college students' intercultural dating behaviors and attitudes found that 90% of White men and 70% of Black men viewed Latinas as an attractive intercultural dating partner, whereas 60% of White men and 52% of Latino men viewed Black women as an attractive intercultural dating partner [31]. Much of this may be accounted for by the fact that many Latinas match the idealized popular image of American female beauty [26,31,32].…”
Section: Latino/a Students and Intercultural Datingmentioning
confidence: 99%
“…These factors include: length of time in the U.S., low levels of ethnic identification, high levels of English language acculturation, ethnically diverse social networks, and low ingroup bias and intergroup anxiety [26,32,36,37]. Research on rates of actual intercultural dating is mixed.…”
Section: Latino/a Students and Intercultural Datingmentioning
confidence: 99%
“…The effect of a premarital birth among cohabitating Hispanic couples on future marriage also differs, with an increased likelihood to marry for Mexican Americans and a decreased likelihood for Puerto Ricans to wed (Manning & Landale, 1996). Stephens, Fernandez, and Richman (2012) also found that Hispanic women with darker skin viewed themselves as less attractive, and were viewed as more likely to engage in sexual risk taking.…”
Section: Social Learning Theorymentioning
confidence: 92%
“…Parental interactions influence daughters' ideas about themselves as a member of a relationship dyad (O'Sullivan et al, 2001;Raffaelli, & Ontai, 2001;Stephens et al, 2012). This becomes even more salient when examining populations where parental values are viewed as valuable and central to intimate relationship formation, as noted in Hispanic populations (Alleyne-Green et al, 2012;Castillo, Perez, Castillo, & Ghosheh, 2010).…”
Section: Parental Influencementioning
confidence: 99%
“…Prior research in this area has largely focused on the influence of parental socialization and modeling processes on victimization and perpetration. This is because as the most proximal influence on their children, parents' behaviors serve as guidelines and examples that prepare them for intimate relationships (O'Sullivan, MeyerBahlburg, & Watkins, 2001;Raffaelli, & Ontai, 2001;Stephens, Fernandez, & Richman, 2012). Specifically, the Social Learning Theory-based IPV research suggests that children learn appropriate relationship behaviors directly by observing the ways their parents interact (Bandura, 1973;Halford, Sanders, & Behrens, 2000;Hines & Saudino, 2002;Kalmuss, 1984;Palazzolo, Roberto, & Babin, 2010;Skuja & Halford, 2004).…”
Section: Introductionmentioning
confidence: 99%